Breaking the Patriarchal Mold: A Journal on Feminism, Singleness, and Women’s Empowerment in Jakarta - Angellica (Ilomata International Journal of Social Science, 2024)
In Indonesia, patriarchal norms and societal expectations significantly constrain women's agency and autonomy, particularly in the context of singleness. However, research on the experiences of single women in Jakarta is notably limited within academic discourse. Breaking the Patriarchal Mold aims to explore the intersections of feminism, singleness, and women's empowerment in Jakarta. The primary objective is to challenge and dismantle patriarchal norms while amplifying the voices of marginalized single women. The journal invites submissions from various theoretical perspectives, including feminist theory, intersectional feminism, queer feminism, and postcolonial feminism. These perspectives will be utilized to examine and contextualize the experiences of single women in Jakarta. Breaking the Patriarchal Mold will feature scholarly articles, personal essays, and creative works that delve into the experiences of single women in Jakarta. It is anticipated that the journal will shed light on the diverse experiences of single women in Jakarta and provide insights into how patriarchal norms and societal expectations impact their lives. The journal's findings will contribute to the broader discourse on feminism, singleness, and women's empowerment in Indonesia. Additionally, it will promote gender equality and social justice in the region. Breaking the Patriarchal Mold will serve as a platform to elevate the voices of single women in Jakarta, challenge prevailing patriarchal structures, and advocate for greater gender equality and social change.